2020
DOI: 10.1021/acs.est.0c03315
|View full text |Cite|
|
Sign up to set email alerts
|

Gene-Centric Model Approaches for Accurate Prediction of Pesticide Biodegradation in Soils

Abstract: Pesticides are widely used in agriculture despite their negative impact on ecosystems and human health. Biogeochemical modeling facilitates the mechanistic understanding of microbial controls on pesticide turnover in soils. We propose to inform models of coupled microbial dynamics and pesticide turnover with measurements of the abundance and expression of functional genes. To assess the advantages of informing models with genetic data, we developed a novel “gene-centric” model and compared model variants of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 101 publications
1
24
0
Order By: Relevance
“…The lack of obvious correlations between transcripts of functional genes and reaction rates observed in our modeling results are likely representative for such dynamic environments. A non-linear, hysteretic relationship between transcript concentrations and reaction rates has also been found in a gene-centric model of pesticide degradation (Chavez Rodriguez et al, 2020). Interestingly, this is the case although pesticide degradation acts on much longer time scales than denitrification in this study and the observed relationship between rates and transcripts shows different patterns than the ones presented in Figure 4 (e.g., direction of the hysteresis).…”
Section: Relationship Between Reaction Rates and Transcript Concentrationssupporting
confidence: 63%
See 2 more Smart Citations
“…The lack of obvious correlations between transcripts of functional genes and reaction rates observed in our modeling results are likely representative for such dynamic environments. A non-linear, hysteretic relationship between transcript concentrations and reaction rates has also been found in a gene-centric model of pesticide degradation (Chavez Rodriguez et al, 2020). Interestingly, this is the case although pesticide degradation acts on much longer time scales than denitrification in this study and the observed relationship between rates and transcripts shows different patterns than the ones presented in Figure 4 (e.g., direction of the hysteresis).…”
Section: Relationship Between Reaction Rates and Transcript Concentrationssupporting
confidence: 63%
“…Here, we apply our model to a dynamic reactive system, that is, one with shifts in the predominant electron accepting species, and inform it with a highly temporally resolved dataset of transcript abundances. Previous studies have highlighted a potentially hysteretic relationship between transcript concentrations and reaction rates (Baelum et al, 2008;Chavez Rodriguez et al, 2020). Our model allows us to further explore the relationship between transcripts, enzymes, and reaction rates and develop mechanistic interpretations of the observations.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Under extreme electron‐donor limitation, our model predicts very low absolute transcript concentrations even without explicitly accounting for DOC‐controlled downregulation of transcription because DOC‐limitation restricts microbial growth, leading to low biomass and, thereby, low transcript concentrations. However, if there is evidence for a large abundance of inactive denitrifiers, the model might need to distinguish between the active and an inactive microbial pool, in which transcription is shut off (e.g., Chavez Rodriguez et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Pesticide utilization varied by province, however, the principal pesticides being used are constant across the area but were also connected with wheat as well as canola plants. Chavez Rodriguez et al [18] developed gene-centric frameworks of combined microbial dynamics as well as pesticide degradation relying on assessments of genetic abundance & function. Utilizing such an informative paradigm towards genetic data.…”
Section: Literature Reviewmentioning
confidence: 99%